Penerapan teori belajar kognitivisme dalam pembelajaran di madrasah ibtidaiyah - Ikhsan, Nabila Aulia (Maliki Interdisciplinary Journal, 2026)
This study discusses the application of cognitivism in learning at Islamic Elementary Schools (Madrasah Ibtidaiyah) as an effort to improve students’ concepts and thinking skills. This is because the cognitive approach emphasizes mental processes such as memory, perception, and reasoning, so that learning focuses not only on delivering material or information, but also on how students process and combine new information with existing information. In the context of Islamic Elementary Schools, the application of this theory is through the use of learning strategies that encourage mental activities such as problem-solving, discussion, the use of concrete media, and reinforcement of previous learning experiences. The study shows that the application of cognitive learning theory can increase learning independence, student engagement, and student memory. This study also emphasizes the importance of the teacher’s role in designing learning that is appropriate to the stage of students’ cognitive development so that the teaching and learning process is more active, effective, and meaningful